Tirtawening Bottled Water Sales in Regional Government-Owned Enterprise: Influences of Brand Image and Digital Marketing - Ooy Siti Halimah; Anneu Siti Hafsah; Taufiq Rahmat (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Abstract This study investigates the influence of brand image and digital marketing on the sales volume of Watermed and Hanaang bottled drinking water produced by Perumda Tirtawening, a regional government-owned enterprise in Bandung. The research adopts a descriptive method with a quantitative approach. The target population consists of consumers who purchase Watermed and Hanaang products from Perumda Tirtawening. Data was collected through an online questionnaire, and a sample of 64 respondents was determined using the Slovin formula. Data analysis was conducted using descriptive statistics and classical assumption tests with SPSS 26.0 software. The results reveal that both brand image and digital marketing have a significant positive effect on sales volume, both individually and collectively. Specifically, brand image accounts for 4.21% of the variation in sales volume, while digital marketing has a more substantial impact, contributing 78.73%. The total effect of brand image and digital marketing on sales volume, indicated by the coefficient of determination (R²), is 0.789, or 78%. This suggests that 78% of the variation in sales volume can be explained by brand image and digital marketing, with other external factors influencing the remaining 22%. The findings indicate that the model developed in this study is strong and reliable. Consequently, brand image and digital marketing are key variables in understanding the structure of bottled water sales volume in Perumda Tirtawening. The unexplained 22% variation may be attributed to other factors not included in this study, such as interactive relationships, incentive programs, website design, and promotional strategies. Keywords: Brand Image, Digital Marketing, Sales Volume